Should Partial Hydrolysates Be Used as Starter Infant Formula? A Working Group Consensus. Issue 1 (January 2016) - Vandenplas, Yvan; Alarcon, Pedro; Fleischer, David; Hernell, Olle; Kolacek, Sanja; Laignelet, Hugo; Lönnerdal, Bo; Raman, Rita; Rigo, Jacques; Salvatore, Silvia; Shamir, Raanan; Staiano, Annamaria; et al.
Abstract : ABSTRACT: Partially hydrolyzed formulas (pHFs) are increasingly used worldwide, both in the prevention of atopic disease in at-risk infants and in the therapeutic management of infants with functional gastrointestinal manifestations. Because prevention is always preferable to treatment, we reviewed the literature aiming to find an answer for the question whether pHF may be recommended for feeding all infants if breast-feeding is not possible. PubMed and Cochrane databases were searched up to December 2014. In addition, to search for data that remained undetected by the searches, we approached authors of relevant articles and major producers of pHFs asking for unpublished data. Because few data were found, nonrandomized, controlled trials and trials in preterm infants were included as well. Overall, only limited data could be found on the efficacy and safety of pHF in healthy term infants. Available data do not indicate that pHFs are potentially harmful for healthy, term infants. With respect to long-term outcomes, particularly referring to immune, metabolic and hormonal effects, data are, however, nonexistent. From a regulatory point of view, pHFs meet the nutrient requirements to be considered as standard formula for term healthy infants. Cost, which is different from country to country, should be considered in the decision-making process. Based on limited available data, the use of pHF in healthy infants is safe with regard to growth. The lack of data, in particular for metabolic consequences and long-term outcomes, is, however, the basis for our recommendation that health authorities should develop and support long-term follow-up studies. Efficacy and long-term safety data are required before a recommendation of this type of formula for all infants can be made. Abstract : Supplemental Digital Content is available in the text